Silicon composite material and preparation method thereof, negative pole piece, secondary battery and electric device
By using a silicon composite material containing one-dimensional conductive material and silicon-based material in the negative electrode sheet of lithium-ion batteries, the problem of poor circulation and fast charging performance of silicon-based materials in lithium-ion batteries is solved, and more efficient construction of conductive networks and battery performance improvements are achieved.
Patent Information
- Application Number
- CN202311129434.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-04
AI Technical Summary
The cycling performance and fast charging performance of silicon-based materials in lithium-ion batteries still need to be improved, mainly because the volume of silicon-based materials changes greatly during charging and discharging, resulting in insufficient conductive network, which affects the efficient use of the battery.
A silicon composite material is used, which includes a one-dimensional conductive material, an inner core and a cladding layer. The cladding layer is coated on the outer surface of the inner core, and the one-dimensional conductive material is arranged on the outer surface of the cladding layer. The inner core comprises a silicon-based material. This structure reduces entanglement and agglomeration between the conductive materials, improves electrical contact between the particles of the negative electrode active material, and forms a more effective conductive network by providing a one-dimensional conductive material on the outer surface of the cladding layer.
This silicon composite material significantly improves the circulation and fast charging performance of lithium-ion batteries, ensuring the stability and performance of the battery during efficient charging and discharging.
Smart Images

Figure BDA0004429797910000161 
Figure BDA0004429797910000171 
Figure BDA0004429797910000172
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a silicon composite material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density and cycle performance.
[0004] Silicon-based materials have attracted attention due to their much higher capacity than carbon-based materials, as higher capacity means higher energy density can be achieved. However, the cycle performance and fast charging performance of batteries containing silicon-based materials still need to be further improved. Summary of the invention
[0005] The present application provides a silicon composite material with good cycle performance and fast charging performance and a preparation method thereof, as well as a negative electrode plate, a secondary battery and an electrical device using the silicon composite material.
[0006] In a first aspect of the present application, a silicon composite material is provided, comprising a one-dimensional conductive material, an inner core and a coating layer, wherein the coating layer is coated on the outer surface of the inner core, the one-dimensional conductive material is arranged on the outer surface of the coating layer, and the inner core comprises a silicon-based material.
[0007] The above-mentioned silicon composite material arranges the one-dimensional conductive material on the outer surface of the coating layer of the silicon-based material, thereby comprehensively improving the cycle performance and fast charging performance.
[0008] In some of the embodiments, the one-dimensional conductive material extends outward from an outer surface of the cladding layer.
[0009] In some of the embodiments, the outer surface of the coating layer further has catalyst particles, and the one-dimensional conductive material is disposed on the surface of the catalyst particles;
[0010] Optionally, the catalyst particles include transition metal nanoparticles;
[0011] Further optionally, the transition metal nanoparticles include one or more of iron nanoparticles, cobalt nanoparticles and nickel nanoparticles;
[0012] Optionally, the coating layer comprises a carbon coating layer;
[0013] Further optionally, the carbon coating layer includes amorphous carbon.
[0014] In some of the embodiments, the mass percentage of the catalyst particles is 0.001% to 0.3% based on the mass of the silicon-based material.
[0015] In some embodiments, the one-dimensional conductive material includes carbon nanotubes;
[0016] Optionally, the carbon nanotubes have one or more of the following characteristics:
[0017] (1) The average tube length is 0.5 μm to 10 μm; optionally, the average tube length of the carbon nanotubes is 1 μm to 10 μm;
[0018] (2) The average tube diameter is 1 nm to 50 nm; optionally, the average tube diameter of the carbon nanotubes is 20 nm to 30 nm.
[0019] In some of the embodiments, based on the mass of the silicon-based material, the mass percentage of the one-dimensional conductive material is 0.01% to 5%; optionally, the mass percentage of the catalyst particles is 0.4% to 5%.
[0020] In some embodiments, the Dv50 of the silicon composite material is 1 μm to 30 μm.
[0021] In some embodiments, the silicon-based material includes one or more of silicon-oxygen compounds, silicon-carbon composites, elemental silicon, or silicon alloys.
[0022] A second aspect of the present application provides a method for preparing a silicon composite material, comprising the following steps:
[0023] preparing a coating layer on the outer surface of an inner core, wherein the inner core comprises a silicon-based material;
[0024] A one-dimensional conductive material is prepared on the outer surface of the coating layer.
[0025] The preparation method is simple in steps and is easy to promote and apply industrially. At the same time, the preparation method prepares a one-dimensional conductive material on the outer surface of the coating layer, which reduces the problem of slurry gel and agglomeration caused by adding a one-dimensional conductive material to the slurry, making the process of the negative electrode sheet easy to carry out.
[0026] In some embodiments, preparing a one-dimensional conductive material on the outer surface of the coating layer comprises the following steps:
[0027] preparing catalyst particles on the outer surface of the coating layer;
[0028] preparing a one-dimensional conductive material on the surface of the catalyst particles;
[0029] Optionally, the catalyst particles include transition metal nanoparticles;
[0030] Further optionally, the transition metal nanoparticles include one or more of iron nanoparticles, cobalt nanoparticles and nickel nanoparticles.
[0031] In some embodiments, preparing catalyst particles on the outer surface of the coating layer comprises the following steps:
[0032] Preparing transition metal oxide and / or transition metal hydroxide on the surface of the coating layer;
[0033] Calcination is performed under a reducing atmosphere to convert the transition metal oxide and / or transition metal hydroxide into transition metal nanoparticles;
[0034] Optionally, the calcination temperature is 600°C to 800°C.
[0035] In some of the embodiments, the one-dimensional conductive material is in-situ grown on the surface of the catalyst particles.
[0036] In some embodiments, the one-dimensional conductive material comprises carbon nanotubes, and preparing the one-dimensional conductive material on the surface of the catalyst particles comprises the following steps:
[0037] introducing a carbon source gas to in-situ grow the carbon nanotubes on the surface of the catalyst particles;
[0038] Optionally, the carbon source gas includes hydrocarbon gas; further optionally, the carbon source gas includes one or more of CH4, C2H2 and propylene.
[0039] In a third aspect of the present application, a negative electrode plate is provided, comprising a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises one or more of the silicon composite material described in the first aspect or the silicon composite material prepared by the preparation method described in the second aspect.
[0040] In some embodiments, the negative electrode active material layer further comprises a carbon-based material;
[0041] Optionally, the mass ratio of the silicon composite material to the carbon-based material is (10% to 90%): (90% to 10%).
[0042] A fourth aspect of the present application provides a secondary battery comprising the negative electrode sheet described in the third aspect.
[0043] In a fifth aspect of the present application, there is provided an electrical device comprising one or more of the negative electrode sheet described in the third aspect or the secondary battery described in the fourth aspect.
[0044] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0046] Figure 1 A schematic diagram of a battery cell according to an embodiment of the present application;
[0047] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0048] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0049] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application;
[0050] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0051] Figure 6 A schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;
[0052] Figure 7 This is a surface electron microscope image of a silicon composite material with in-situ CNT growth prepared in one embodiment of the present application;
[0053] Description of reference numerals:
[0054] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION
[0055] Below, some embodiments of the silicon composite material and its preparation method, negative electrode plate, secondary battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0056] The "range" disclosed in the present application can be defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and any end value can be included or excluded independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0057] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0058] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0059] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0060] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0061] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0062] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0063] Silicon-based materials will produce huge volume changes (>300%) during the charging and discharging process, which is much higher than carbon-based materials. The traditional conductive agent is in point contact with the negative electrode active material particles. After the silicon-based material expands, the gaps between the particles are large, so it is impossible to form an effective conductive network, which in turn significantly reduces its fast charging performance and cycle performance.
[0064] There is a plan to improve this problem by adding carbon nanotubes (CNT) to the material. However, due to the small number of surface defects and lack of active groups, the solubility of carbon nanotubes in various solvents is very low. In addition, carbon nanotubes are composed of graphite with a lamellar structure, and the sp2 hybridization of carbon atoms forms highly delocalized electrons. There is a large van der Waals attraction between carbon nanotubes, and the specific surface area and aspect ratio are relatively large. Therefore, carbon nanotubes generally exist in the form of entangled aggregates. Adding carbon nanotubes at the slurry level will bring a series of problems, such as slurry gel, agglomeration, and poor dispersion effect. In addition, since carbon nanotubes and carbon-based materials such as graphite are hybridized, after the slurry is coated to form a pole piece, at the pole piece level, carbon nanotubes are more likely to adhere and agglomerate on the surface of the carbon-based material, while there are relatively few carbon nanotubes on the surface of the silicon-based material, and it is difficult to improve the conductive network of the silicon-based material and achieve long-range conductivity of the silicon-based material.
[0065] There is also a proposal to provide a composite material, which uses carbon material to jointly coat physically mixed carbon nanotubes and silicon-based materials. Although this allows the carbon nanotubes to be dispersed inside the carbon coating layer to reduce their agglomeration, the carbon nanotubes dispersed inside the carbon coating layer can only play the role of connecting the silicon-based materials inside the negative electrode active material particles, and have little effect on constructing a conductive network between multiple negative electrode active material particles. In particular, during the charge and discharge process, after the negative electrode active material particles expand, it is difficult to achieve good electrical contact between the multiple negative electrode active material particles to form an effective conductive network. Therefore, this solution has little effect on improving the cycle performance and fast charging performance of the secondary battery.
[0066] Based on this, some examples of the present application provide a silicon composite material, including a one-dimensional conductive material, an inner core and a coating layer, wherein the coating layer is coated on the outer surface of the inner core, the one-dimensional conductive material is arranged on the outer surface of the coating layer, and the inner core contains a silicon-based material.
[0067] The above-mentioned silicon composite material arranges the one-dimensional conductive material on the outer surface of the coating layer of the silicon-based material. This can, on the one hand, reduce the entanglement and agglomeration between the one-dimensional conductive materials, thereby reducing the problems of slurry gelation, agglomeration and poor dispersion in the preparation process of the negative electrode plate; on the other hand, the one-dimensional conductive material arranged on the outer surface of the coating layer can improve the electrical contact between multiple negative electrode active material particles. Even if the negative electrode active material particles at the plate level expand during the charging and discharging process, an effective conductive network can still be constructed between the particles, thereby comprehensively improving the cycle performance and fast charging performance.
[0068] It can be understood that the coating layer preferably continuously and completely coats the outer surface of the inner core containing the silicon-based material, while the coating layer also does not exclude the possibility of discontinuous or partial coating on the outer surface of the inner core.
[0069] It can be understood that the material composition of the one-dimensional conductive material and the coating layer may be the same, or different or partially the same. Preferably, the material composition of the one-dimensional conductive material and the coating layer is the same.
[0070] It can be understood that “the one-dimensional conductive material is disposed on the outer surface of the coating layer” may mean that the one-dimensional conductive material is directly disposed on the outer surface of the coating layer without an intermediate connecting unit, or may mean that the one-dimensional conductive material is disposed on the outer surface of the coating layer through an intermediate connecting unit. In some examples of the present application, the intermediate connecting unit may be a catalyst particle.
[0071] In some of the examples, the one-dimensional conductive material extends outward from the outer surface of the coating layer. The one-dimensional conductive material is formed on the surface of the coating layer and can fully extend and disperse outward, which is conducive to the construction of a conductive network between particles and improves the cycle performance and fast charging performance.
[0072] It can be understood that the coating layer may include a single-layer coating layer or a multi-layer coating layer.
[0073] In some examples, the outer surface of the coating layer also has catalyst particles, and the one-dimensional conductive material is disposed on the surface of the catalyst particles. Without limitation, the presence of catalyst characteristic elements can be characterized by methods such as ICP.
[0074] Furthermore, the catalyst particles include transition metal nanoparticles.
[0075] In some examples, the transition metal nanoparticles include one or more of iron nanoparticles, cobalt nanoparticles and nickel nanoparticles. Selecting appropriate transition metal nanoparticles is conducive to improving the stability of the structure, thereby improving the cycle life. It is understandable that the iron nanoparticles, cobalt nanoparticles and nickel nanoparticles are all metal elemental particles. Further, the transition metal nanoparticles include one or more of cobalt nanoparticles and nickel nanoparticles.
[0076] In some examples, the coating layer includes a carbon coating layer. Coating the inner core with the carbon coating layer is beneficial to further improve the conductivity between particles. Without limitation, the carbon coating layer includes amorphous carbon.
[0077] In some of the examples, the mass percentage of the catalyst particles is 0.001% to 0.3% based on the mass of the silicon-based material. Reasonable control of the mass percentage of the catalyst particles can regulate the content and distribution of the one-dimensional conductive material, so that it can be more fully stretched and dispersed, which is beneficial to improve the cycle performance and fast charging performance. Specifically, the mass percentage of the catalyst particles includes but is not limited to: 0.001%, 0.005%, 0.01%, 0.015%, 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3% or a range between any two of the foregoing. Furthermore, the mass percentage of the catalyst particles is 0.05% to 0.3%.
[0078] It can be understood that the one-dimensional conductive material refers to a one-dimensional material with conductivity. One-dimensional material refers to a linear material. For example, in a whisker, atoms are regularly arranged in one direction to the order of micrometers to centimeters, and in the other two directions, there are only a few atoms arranged, which are nanometers. Accordingly, electrons basically only move in a straight line in one nanometer scale direction. One-dimensional materials include nanobelts, nanotubes, quantum wire materials, etc. Without limitation, the one-dimensional conductive material can be exemplified by carbon nanotubes, metal nanofibers, one-dimensional conductive polymer nanomaterials, etc.
[0079] In some examples, the one-dimensional conductive material includes carbon nanotubes.
[0080] Furthermore, the average tube length of the carbon nanotubes is 0.5μm to 10μm. Reasonable control of the tube length of the carbon nanotubes is beneficial to the construction of a conductive network between the particles of the negative electrode active material, and on the other hand, it reduces the possibility of entanglement and agglomeration between the carbon nanotubes, thereby improving the fast charging performance and cycle performance. Specifically, the average tube length of the carbon nanotubes includes but is not limited to: 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm or a range between any two of the foregoing. Furthermore, the average tube length of the carbon nanotubes is 1μm to 10μm.
[0081] Furthermore, the average diameter of the carbon nanotubes is 1nm to 50nm. Reasonable control of the diameter of the carbon nanotubes is conducive to improving the cycle performance. Specifically, the average diameter of the carbon nanotubes includes but is not limited to: 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm or a range between any two of the foregoing. Furthermore, the average diameter of the carbon nanotubes is 20nm to 30nm.
[0082] In some of the examples, the mass percentage of the one-dimensional conductive material is 0.01% to 5% based on the mass of the silicon-based material. Reasonable control of the mass percentage of the one-dimensional conductive material is beneficial to the construction of a conductive network between the particles of the negative electrode active material, and on the other hand, it reduces the possibility of entanglement and agglomeration between the one-dimensional conductive materials. Specifically, the mass percentage of the one-dimensional conductive material includes but is not limited to: 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range between any two of the foregoing. Furthermore, the mass percentage of the one-dimensional conductive material is 0.4% to 5%.
[0083] In some of the examples, the Dv50 of the silicon composite material is 1μm to 30μm. The silicon composite material has a good size and good size uniformity. The Dv50 of the silicon composite material is within the above range. On the one hand, it is beneficial to improve ion conductivity, reduce internal resistance during discharge, and increase material life; on the other hand, it enables the material to have a suitable specific surface area, reduce particle agglomeration during processing and improve storage performance. Specifically, the Dv50 of the silicon composite material includes but is not limited to: 1μm, 5μm, 8μm, 10μm, 15μm, 20μm, 25μm, 30μm or a range between any two of the foregoing.
[0084] In addition, without limitation, the silicon-based material includes one or more of silicon oxide compounds (SiOx, 0<x<2), silicon carbon composites, elemental silicon or silicon alloys.
[0085] It can be understood that the structure of the silicon oxide compound (SiOx, 0<x<2) and the silicon carbon composite is a coating structure, a supporting structure or a dispersed structure.
[0086] In some examples of the present application, the silicon-based material includes a silicon-oxygen compound with a loaded structure, and the silicon-oxygen compound is specifically a composite material formed by nano-silicon particles loaded in a silicon dioxide matrix.
[0087] In some examples of the present application, the silicon-based material includes a silicon-oxygen compound with a coating structure, and the silicon-oxygen compound is specifically an outer layer of silicon monoxide coated with a layer of carbon-based material as a protective layer.
[0088] In some examples of the present application, the silicon-based material includes a silicon-carbon composite with a coating structure, and the silicon-carbon compound is specifically an outer layer of elemental silicon and / or silicon alloy coated with a layer of carbon-based material as a protective layer.
[0089] In some examples of the present application, the silicon-based material includes a silicon-carbon composite with a dispersed structure, and the silicon-carbon composite is specifically a composite system in which a single silicon and / or silicon alloy inner core and a carbon-based inner core form physical contact and uniformity.
[0090] In some other examples of the present application, a method for preparing a silicon composite material is provided, comprising the following steps:
[0091] preparing a coating layer on the outer surface of an inner core, wherein the inner core comprises a silicon-based material;
[0092] A one-dimensional conductive material is prepared on the outer surface of the coating layer.
[0093] The preparation method is simple in steps and is easy to promote and apply industrially. At the same time, the preparation method prepares a one-dimensional conductive material on the outer surface of the coating layer, which reduces the problem of slurry gel and agglomeration caused by adding a one-dimensional conductive material to the slurry, making the process of the negative electrode sheet easy to carry out.
[0094] It can be understood that the silicon composite material in the preparation method has the same or similar technical solutions and effects as the aforementioned silicon composite material, which will not be described in detail herein.
[0095] In some examples, preparing a one-dimensional conductive material on the outer surface of the coating layer includes the following steps:
[0096] preparing catalyst particles on the outer surface of the coating layer;
[0097] A one-dimensional conductive material is prepared on the surface of the catalyst particles.
[0098] In some examples, preparing catalyst particles on the outer surface of the coating layer includes the following steps:
[0099] Preparing transition metal oxide and / or transition metal hydroxide on the surface of the coating layer;
[0100] The transition metal oxide and / or transition metal hydroxide is calcined in a reducing atmosphere to generate transition metal nanoparticles.
[0101] In some examples, the calcination temperature is 600°C to 800°C.
[0102] In some of the examples, preparing transition metal oxides and / or transition metal hydroxides on the surface of the sub-coating layer includes: mixing an inner core whose surface is coated with the sub-coating layer with a solution of a transition metal salt to generate transition metal oxides and / or transition metal hydroxides on the surface of the sub-coating layer.
[0103] In some examples, the one-dimensional conductive material is in-situ grown on the surface of the catalyst particles. Through in-situ growth, the one-dimensional conductive material is distributed more uniformly and can even be arranged in a directional manner.
[0104] In some examples, the one-dimensional conductive material includes carbon nanotubes, and preparing the one-dimensional conductive material on the surface of the catalyst particles includes the following steps:
[0105] A carbon source gas is introduced to in-situ grow the carbon nanotubes on the surface of the catalyst particles.
[0106] Without limitation, the carbon source gas includes hydrocarbon gas. Further, the carbon source gas includes one or more of CH4, C2H2 and propylene.
[0107] Without limitation, the temperature condition for preparing the one-dimensional conductive material on the surface of the catalyst particles is 500° C. to 800° C.
[0108] Without limitation, the flow rate of the carbon source gas is 0.5 to 1.5 L / min, and the reaction time is 0.5 h to 5 h.
[0109] Some other examples of the present application provide a negative electrode plate, including a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes one or more of the silicon composite materials as described above or the silicon composite materials prepared by the preparation method as described above.
[0110] In some examples, the negative electrode active material layer further includes a carbon-based material.
[0111] Without limitation, the mass ratio of the silicon composite material to the carbon-based material is (10% to 90%): (90% to 10%). Specifically, the mass ratio includes but is not limited to: 10%: 90%, 20%: 80%, 30%: 70%, 40%: 60%, 50%: 50%, 60%: 40%, 70%: 30%, 80%: 20%, 90%: 10% or a range between any two of the foregoing. Further, the mass ratio of the silicon composite material to the carbon-based material is (10% to 50%): (90% to 50%).
[0112] Some other examples of the present application provide a secondary battery, comprising the negative electrode sheet as described above.
[0113] Some other examples of the present application provide an electrical device including one or more of the negative electrode plate as described above or the secondary battery as described above.
[0114] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0115] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0116] Positive electrode
[0117] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode material, and non-limiting examples include coating modification.
[0118] In the list of positive electrode materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.
[0119] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0120] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0121] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0122] In some of the embodiments, the positive electrode active material may be a positive electrode active material for a battery known in the art. As a non-limiting example, the positive electrode active material may include one or more of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.15 Al 0.05 O2.
[0123] In some of these embodiments, the positive electrode active material layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0124] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0125] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt% to 80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000 to 25000 mPa·s. When the positive electrode slurry is applied, the coating unit surface density based on dry weight (excluding solvent) can be 15 to 35 mg / cm 2The compaction density of the positive electrode sheet can be 3.0 to 3.6 g / cm 3 , can be selected as 3.3~3.5g / cm 3 .
[0126] Negative electrode
[0127] The negative electrode plate is as described above.
[0128] In addition, as a non-limiting example, the negative electrode current collector has two surfaces facing each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two facing surfaces of the negative electrode current collector.
[0129] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0130] In some of the embodiments, the negative electrode active material layer may also include other negative electrode active materials for batteries known in the art. As non-limiting examples, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0131] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0132] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0133] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0134] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt% to 60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000 to 10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75 to 220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8g / cm 3 .
[0135] Electrolytes
[0136] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0137] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0138] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0139] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0140] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0141] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0142] Isolation film
[0143] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0144] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0145] In some embodiments, the isolation film has a thickness of 6 to 40 μm, and may be 12 to 20 μm.
[0146] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0147] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0148] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0149] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.
[0150] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0151] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 1 The battery cell 5 is a square structure as an example.
[0152] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.
[0153] The secondary battery may be a battery module 4 or a battery pack 1 .
[0154] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.
[0155] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0156] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0157] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0158] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0159] In addition, the present application also provides an electrical device, which includes a secondary battery provided by the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.
[0160] As an electrical device, a secondary battery can be selected according to its usage requirements.
[0161] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0162] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0163] Example
[0164] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0165] Example 1
[0166] 1) Preparation of positive electrode
[0167] The positive electrode active material NCM811, the conductive carbon black SP and the binder PVDF were dispersed in the solvent NMP in a weight ratio of 98:1:1 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the double-sided surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained, wherein the coating amount per unit area of both sides was 0.27g / 1540.25mm 2 .
[0168] 2) Preparation of negative electrode sheet
[0169] 2.1 Preparation of negative electrode active materials
[0170] Amorphous carbon-coated pure silicon material (commercially available product, wherein the mass percentage of pure silicon is 95%) is used as raw material, and ultrasonic dispersion is carried out in an ethanol aqueous solution of FeCl3 (volume ratio 1:1), and iron oxide is generated on the surface of the amorphous carbon-coated pure silicon material. The product is then calcined at a high temperature of 700°C and in a reducing atmosphere (argon: hydrogen = 95:5, volume ratio) to generate iron nanoparticles (the mass percentage of the iron nanoparticles is 0.15% based on the mass of pure silicon). Using iron nanoparticles as a catalyst, carbon source gas C2H2 is introduced at a flow rate of 1L / min, and the reaction is carried out at a constant temperature of 700°C for 3h, and then naturally cooled to obtain a silicon composite material with in-situ CNT growth, with a particle size Dv50 of 8μm, wherein the average tube length of the CNT is 5μm, the average tube diameter is 25nm, and the mass percentage of the CNT is 2% based on the mass of pure silicon. At the same time, the surface electron microscope image of the silicon composite material with in-situ CNT growth is as follows Figure 7 As shown, it can be seen that the CNTs extend outward from the outer surface of the amorphous carbon coating layer, rather than being closely attached to the surface of the carbon coating layer or fused with the carbon coating layer.
[0171] 2.2. The negative electrode active material (the silicon material (silicon composite material) for in-situ growth of CNT prepared in step 2.1 and graphite (carbon-based material) are mixed in a mass ratio of 20%:80%), a thickener sodium carboxymethyl cellulose, an adhesive styrene butadiene rubber, and a conductive agent acetylene black are mixed in a mass ratio of 97:1:1:1, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on both sides of the copper foil; the copper foil is dried at room temperature and then transferred to a 120°C oven for drying for 1 hour, and then super-cold pressed and cut to obtain a negative electrode sheet, wherein the coating amount per unit area on both sides is 0.17 g / 1540.25 mm 2 .
[0172] 3) Isolation film
[0173] A 12μm thick polypropylene isolation film was selected.
[0174] 4) Preparation of electrolyte
[0175] The organic solvent is a mixed solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.
[0176] 5) Preparation of batteries
[0177] The positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role. Then, they are wound into a square bare battery cell, loaded with aluminum-plastic film, and then baked at 80°C to remove water. After that, 10g of the corresponding non-aqueous electrolyte is injected and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a finished battery with a capacity of 4000mAh is obtained.
[0178] The secondary batteries of Examples 2 to 23 are similar to the secondary battery preparation methods of Example 1, and the main differences are the types and proportions of materials, as shown in Table 1 below. Among them, the average tube length and average tube diameter of the carbon nanotubes can be controlled by adjusting parameters such as temperature, flow rate of carbon source gas, and time.
[0179] The preparation methods of the secondary batteries of Examples 24 to 27 are similar to those of Example 1, with the main difference being that the mass ratios of the silicon composite material to the carbon-based material are 10%:90%, 90%:10%, 50%:50%, and 65%:35%, respectively.
[0180] The preparation method of the secondary battery of Comparative Example 1 is similar to that of the secondary battery of Example 1, the main difference being that the preparation of the silicon composite material for in-situ growth of CNTs in step 2.1 is not performed, and in step 2.2, amorphous carbon-coated pure silicon material and graphite are directly mixed in a ratio of 20%:80% as the negative electrode active material, and CNTs accounting for 2% by mass of pure silicon are additionally added to the negative electrode slurry.
[0181] Table 1
[0182]
[0183]
[0184] Test example:
[0185] Test method:
[0186] (1) Fast charging performance:
[0187] At 25°C, take the battery with pre-embedded copper wire and charge it to 4.2V at 0.33C constant current, and continue to charge it at constant voltage until the current is 0.05C. At this time, the battery is fully charged. Record the charging capacity at this time, which is the charging capacity of the first cycle; after the battery is left to stand for 30 minutes, discharge it to 2.8V at 0.33C constant current. This is a cyclic charging and discharging process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Then start lithium plating, connect the copper wire to the positive electrode with the charging device, charge it at a constant current of 20uA for 2h, then connect the copper wire to the negative electrode with the charging device, charge it at a constant current of 20uA for 2h, and the copper wire after lithium plating is the reference electrode. The reference electrode potential defaults to 0mV. After lithium plating, charge the battery at a constant current of 2C, record the potential difference between the anode and the reference electrode, and when the potential difference reaches 0mV, record the ratio of the charged capacity to the charging capacity of the first cycle. This ratio represents the fast charging performance of the battery cell.
[0188] (2) Cycle performance:
[0189] At 25°C, charge the battery to 4.2V at 0.5C constant current, and continue to charge at constant voltage until the current reaches 0.05C. At this time, the battery is fully charged. Record the charging capacity at this time, which is the charging capacity of the first cycle. After the battery is left to stand for 30 minutes, discharge it to 2.8V at 1C constant current. This is a cyclic charge and discharge process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Perform cyclic charge and discharge tests on the battery according to the above method, and record the discharge capacity after each cycle until the discharge capacity of the battery decays to 80% of the discharge capacity of the first cycle. The number of cycles at this time is used to characterize the cycle life of the battery.
[0190] (3) Slurry dispersion: The processed slurry is allowed to stand for 24 hours, and the slurry is stirred up with a stirring rod to observe the slurry flow characteristics. If there is no obvious aggregation or gelation, it is judged as "good".
[0191] The test results are shown in Table 2 below:
[0192] Table 2
[0193]
[0194]
[0195] From the comparison between Examples 1 to 23 and Comparative Example 1, it can be seen that the present application can effectively improve the fast charging performance and cycle performance of the silicon composite material by placing a one-dimensional conductive material on the outer surface of the coating layer. In addition, in terms of the process, the dispersion of each material is good, making the process of the negative electrode plate easy to carry out.
[0196] From the comparison between Examples 1 to 7, it can be seen that reasonable control of the mass percentage of carbon nanotubes is beneficial to further improve the cycle performance and fast charging performance.
[0197] From the comparison between Example 1 and Examples 8 to 9, it can be seen that selecting appropriate transition metal nanoparticles is beneficial to improving the stability of the structure and thus improving the cycle life.
[0198] From the comparison between Example 1 and Examples 10 to 18, it can be seen that reasonable control of the tube length of the carbon nanotubes is beneficial to further improve the cycle performance and fast charging performance.
[0199] From the comparison between Example 1 and Examples 19 to 23, it can be seen that reasonable control of the diameter of the carbon nanotubes is beneficial to improving the cycle performance.
[0200] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.
[0201] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A silicon composite material, characterized in that: It comprises a one-dimensional conductive material, an inner core and a coating layer, wherein the coating layer is coated on the outer surface of the inner core, the one-dimensional conductive material is arranged on the outer surface of the coating layer, and the inner core comprises a silicon-based material.
2. The silicon composite material according to claim 1, characterized in that: The one-dimensional conductive material extends outward from the outer surface of the cladding layer.
3. The silicon composite material according to claim 1 or 2, characterized in that: The outer surface of the coating layer also has catalyst particles, and the one-dimensional conductive material is arranged on the surface of the catalyst particles; Optionally, the catalyst particles include transition metal nanoparticles; Further optionally, the transition metal nanoparticles include one or more of iron nanoparticles, cobalt nanoparticles and nickel nanoparticles; Optionally, the coating layer comprises a carbon coating layer; Further optionally, the carbon coating layer includes amorphous carbon.
4. The silicon composite material according to claim 3, characterized in that: Based on the mass of the silicon-based material, the mass percentage of the catalyst particles is 0.001% to 0.3%.
5. The silicon composite material according to any one of claims 1 to 4, characterized in that: The one-dimensional conductive material includes carbon nanotubes; Optionally, the carbon nanotubes have one or more of the following characteristics: (1) The average tube length is 0.5 μm to 10 μm; optionally, the average tube length of the carbon nanotubes is 1 μm to 10 μm; (2) The average tube diameter is 1 nm to 50 nm; optionally, the average tube diameter of the carbon nanotubes is 20 nm to 30 nm.
6. The silicon composite material according to any one of claims 1 to 5, characterized in that: Based on the mass of the silicon-based material, the mass percentage of the one-dimensional conductive material is 0.01% to 5%; optionally, the mass percentage of the catalyst particles is 0.4% to 5%.
7. The silicon composite material according to any one of claims 1 to 6, characterized in that: The Dv50 of the silicon composite material is 1 μm to 30 μm.
8. The silicon composite material according to any one of claims 1 to 7, characterized in that: The silicon-based material includes one or more of silicon-oxygen compounds, silicon-carbon composites, elemental silicon or silicon alloys.
9. A method for preparing a silicon composite material, characterized in that: The steps include: preparing a coating layer on the outer surface of an inner core, wherein the inner core comprises a silicon-based material; A one-dimensional conductive material is prepared on the outer surface of the coating layer.
10. The method for preparing the silicon composite material according to claim 9, characterized in that: Preparing a one-dimensional conductive material on the outer surface of the coating layer comprises the following steps: preparing catalyst particles on the outer surface of the coating layer; preparing a one-dimensional conductive material on the surface of the catalyst particles; Optionally, the catalyst particles include transition metal nanoparticles; Further optionally, the transition metal nanoparticles include one or more of iron nanoparticles, cobalt nanoparticles and nickel nanoparticles.
11. The method for preparing the silicon composite material according to claim 10, characterized in that: The preparation of catalyst particles on the outer surface of the coating layer comprises the following steps: Preparing transition metal oxide and / or transition metal hydroxide on the surface of the coating layer; Calcination is performed under a reducing atmosphere to convert the transition metal oxide and / or transition metal hydroxide into transition metal nanoparticles; Optionally, the calcination temperature is 600°C to 800°C.
12. The method for preparing the silicon composite material according to claim 10 or 11, characterized in that: The one-dimensional conductive material is in-situ grown on the surface of the catalyst particles.
13. The method for preparing the silicon composite material according to any one of claims 10 to 12, characterized in that: The one-dimensional conductive material includes carbon nanotubes, and preparing the one-dimensional conductive material on the surface of the catalyst particles includes the following steps: introducing a carbon source gas to in-situ grow the carbon nanotubes on the surface of the catalyst particles; Optionally, the carbon source gas includes hydrocarbon gas; further optionally, the carbon source gas includes one or more of CH4, C2H2 and propylene.
14. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises one or more of the silicon composite material according to any one of claims 1 to 8 or the silicon composite material prepared by the preparation method according to any one of claims 9 to 13.
15. The negative electrode sheet according to claim 14, characterized in that: The negative electrode active material layer further includes a carbon-based material; Optionally, the mass ratio of the silicon composite material to the carbon-based material is (10% to 90%): (90% to 10%).
16. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 14 or 15.
17. An electrical device, characterized in that: It comprises one or more of the negative electrode sheet according to claim 14 or 15 or the secondary battery according to claim 16.
Citation Information
Patent Citations
Negative electrode material and preparation method thereof and secondary battery
CN111668474A
Negative pole piece and electrochemical device
CN115966653A
Cited By
Silicon composite material and preparation method therefor, negative electrode sheet, secondary battery, and electric device
EP4654296A1